1261 The Long Term Exhaustion of a Viral Infection. (27th May 2020) - Mulhern, Kellen
Abstract: Introduction: Narcolepsy is a rare condition affecting only 0.02% to 0.18% of United States and Euro-pean populations. Throughout the years, hypersomnolence in the form of narcolepsy or idiopathic hypersomnia has been identified as a post infectious syndrome in rare instances. In this case, we observe a child with excessive daytime sleepiness after an infectious rash. Report of Case: A 4 year old male presented to clinic for evaluation of excessive daytime sleepiness for the past 10 months. At that time, he developed a full body rash that lasted for about 1 week, and was treated with diphenhydramine and prednisone. No imminent cause was identified. For the preced-ing weeks, he was taking frequent and longer naps, and complained of difficulty with keeping his head up and his eyes open. He was evaluated for possible seizures via EEG with no seizure activity seen. Blood work was unremarkable, and a lumbar puncture showed highly elevated IgG for EBV, and low IgM for EBV, indicating a prior infection. His excessive somnolence persistent, and he was referred to undergo actigraphy, poly-somnography (PSG), and a multiple sleep latency test (MSLT). Actigraphy demonstrated disrupt-ed nocturnal sleep, PSG showed an elevated periodic leg movement index of 8.6/hr, and MSLT showed reduced sleep onset latency and sleep onset REM on 2 of 4 naps. During his physical exam, he had drooping eyelids and tongue protrusion, concerning for cataplectic facies, highly suspicious for Narcolepsy Type 1. Further confirmatory testing is pend-ing, including HLA subtype testing and hypocretin levels in CSF. Conclusion: This case shows a strong association with a subacute EBV infection and the development of nar-colepsy. There are multiple cases involving the development of hypersomnolence conditions as a consequence of viral infections. Further cases would be beneficial to form additional associations.